2022
DOI: 10.3390/molecules27020369
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pterostilbene-Induced Cell Death in HT-29 Colon Cancer Cells

Abstract: Pterostilbene is a dietary phytochemical that has been found to possess several biological activities, such as antioxidant and anti-inflammatory. Recent studies have shown that it exhibits the hallmark characteristics of an anticancer agent. The aim of the study was to investigate the anticancer activity of pterostilbene against HT-29 human colon cancer cells, focusing on its influence on cell growth, differentiation, and the ability of this stilbene to induce cell death. To clarify the mechanism of pterostilb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Coinciding with the previous literature [18][19][20][21][22], our tentative bioassay screening found that PTE possessed anti-proliferation properties against MDA-MB-231 (TNBC, IC50 = 63.59 μM) and MCF-7 (ER + BC, IC50 = 44.26 μM) cells. In this research, we aimed to obtain lead chemical entities with improved anti-BC activity through the structural optimization of PTE.…”
Section: Chemistrysupporting
confidence: 75%
See 1 more Smart Citation
“…Coinciding with the previous literature [18][19][20][21][22], our tentative bioassay screening found that PTE possessed anti-proliferation properties against MDA-MB-231 (TNBC, IC50 = 63.59 μM) and MCF-7 (ER + BC, IC50 = 44.26 μM) cells. In this research, we aimed to obtain lead chemical entities with improved anti-BC activity through the structural optimization of PTE.…”
Section: Chemistrysupporting
confidence: 75%
“…Similar to resveratrol, PTE exerts a broad spectrum of biological and pharmacological activities, including antioxidant, anti-inflammatory, anti-fungal, and anti-diabetic capacities [11,[15][16][17]. In addition, PTE has been recognized as a potential antitumor agent against multiple types of cancers, including prostate, liver, lung, gastric, and colon cancer [18][19][20][21][22]. Preliminary investigations of its mechanisms have found that the anticancer behavior of PTE is mainly ascribable to the induction of apoptosis, cell cycle arrest, autophagy, and DNA damage, thus, inhibiting the growth and proliferation of tumor cells [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbene was also reported to induce apoptosis as it increased caspase-3 activity, DNA fragmentation, and the gene expression of BAX. At the higher dose, pterostilbene could regulate autophagy in HT-29 colon cancer cells as pterostilbene increased the gene expression of ULK1 that is responsible for initiating autophagy and increasing gene expression of AMBRA1 and LC3A which are encoded for proteins that are involved in autophagosome formation [124]. Pterostilbene also downregulates the protein expression of anti-apoptotic proteins of Bcl-2 and survivin [121].…”
Section: Other Molecular Mechanisms Of Pterostilbene As An Anti-cance...mentioning
confidence: 99%
“…[21] PSB has also been previously demonstrated to suppress cancer growth and induce cancer cell death via STAT3 pathway inhibition. [22,23] 3'-Hydroxypterostilbene (3HPSB) is an analog of pterostilbene hydroxylated at the 3' position of the B-ring of the stilbene backbone and is naturally found in the Chinese herb Sphaerophysa salsula. [24] 3HPSB has also been identified as a urinary metabolite of pterostilbene in a mouse model.…”
Section: Introductionmentioning
confidence: 99%